Réponses

2014-01-15T02:13:25+01:00
1) A = 0
( y+4 )( 2y-3 ) = 0

Donc
y+4=0
y=-4

Ou 2y-3 = 0
2y=3
y=3/2

2) Soit y = -2
B = y² + 8y + 16
= 4 - 16 + 16
B = 4

3) B = y² + 8y + 16
B = ( y+4 )²

A+B = ( y+4 )( 2y-3 ) + ( y+4 )²
= ( y+4 )( 2y-3+y+4 )
A+B = ( y+4 )( 3y+1 )

A-B = ( y+4 )( 2y-3 ) - ( y+4 )²
= ( y+4 )( 2y-3-y-4 )
A-B = ( y+4 )( y-7 )

4) A+B = ( y+4 )( 3y+1 )
= 3y² + y + 12y + 4
A+B = 3y² + 13y + 4

A-B = ( y+4 )( y-7 )
= y² - 7y + 4y - 28
A-B = y² - 3y - 28

5) B = 0
( y+4 )² = 0
Donc y+4 = 0
y = -4

B = 16
y² + 8y + 16 = 16
y² + 8y = 0
y ( y+8 ) = 0

Donc
y = 0

Ou y+8 = 0
y = -8